AUTHORITY OF DIRECTORATE GENERAL OF SPACE MINISTRY OF WORKGENERAL UNDER THE MINISTRY OF AGRARIAN AND GOVERNANCE / BPN - Hamidah, Upik (Progressive Law Review, 2019)
The rise of the Ministry of Agrarian Affairs and Spatial Planning / BPN in 2015 is a new chapter for BPN institutions. In view of the existence of these ministries, the functions and duties of the Director General of Spatial Planning of the Ministry of Public Works are merged into a ministry institution named the Ministry of Agrarian Affairs and Spatial Planning / BPN. So that change is based on increasing the authority of a state institution, and that authority is increasing and strategic.But in reality in the field, the two ministries are juxtaposed, many are involved. Therefore, it will be discussed in this quiz in accordance with the Regulation of the Director General of Spatial Planning of the Ministry of Public Works who is in charge of the ministry of agrarian affairs and spatial planning / BPN. The purpose of this study is to analyze the authority of the director general of spatial ministry of public works under the ministry of agrarian and spatial planning / BPN.This study uses a normative legal method, with the approach to the legislation and other literature. Based on research results, the authority of the Director General of Spatial Planning of the Ministry of Work under the Ministry of Agrarian Affairs and Spatial Planning / BPN is an institutional opportunity to unify land management comprehensively. The regulation and management of land is not limited to land surface space but encompasses underground space, above ground space, water space and surface space itself, Positive Impact of the existence of the Director General of Spatial Planning under the Ministry of Agrarian Affairs and Spatial Planning / BPN mandates the state to conduct land affairs in a manner to spread includes earth, water, space and natural resources for the greatest prosperity of the people. The Negative Impact of the Authority of the Director General of Spatial Planning under the Ministry of Agrarian Affairs and Spatial Planning / BPN is the need for harmonization of various laws and regulations relating to spatial planning and land management, to facilitate implementation in the field.